Literacy Movement in Kerala One Step Forward, Two Step Backwards - S Mohana Kumar (Economic and Political Weekly October 9, 1993, 1993)
Popular participation and mass involvement which elevated the Total Literacy Programme in Kerala to the level of a mass social movement in its first phase may be undermined because of the politically motivated actions of die Congress government in the state.